Cell‐free DNA 5‐hydroxymethylcytosine as a marker for common cancer detection - Jianming Shao; Eric H. Bernicker; Chuan He; Zejuan Li (Wiley, 2022)
Abstract Background Early cancer detection can dramatically improve clinical outcomes and greatly reduce economic burden of patients. Plasma cell-free DNA (cfDNA) 5‐hydroxymethylcytosine (5hmC) is an emerging epigenetic marker for cancer diagnosis. However, the utility of such marker has not been investigated in many common cancers yet. The purpose of this study was to evaluate 5hmC in plasma cfDNA for an early detection of common cancers. Methods We used a highly sensitive nano‐5hmC‐Seal method and profiled the genome‐wide distribution of 5hmC in plasma cfDNA from 384 patients with bladder, breast, colorectal, kidney, lung or prostate cancer and 221 controls. Genes and signalling pathways with differential hydroxymethylation were analysed. We used machine learning to develop 5hmC signatures for cancer detection and cancer‐origin determination in the training sets and validated the signatures in the validation sets. Results We identified genes and signalling pathways with aberrant DNA hydroxymethylation in six cancers. We discovered a pan‐cancer signature that detected all six cancers with a sensitivity of 68.6% and a specificity of 96.6% and cancer-specific signatures with a sensitivity of 80.0% for breast cancer, 88.9% for kidney cancer, 94.1% for lung cancer and 96.4% for prostate cancer, and a specificity of 100% for all except lung (96.2%). The sensitivity of cancer-specific signatures was 89.3%-100.0% for early‐stage cancers. The lung cancer-specific signature achieved a sensitivity of 98.0% and a specificity of 82.3% in an independent patient cohort with different ethnic backgrounds. Additionally, we discovered a 5hmC signature that could accurately determine cancer origin. Conclusions We demonstrated that plasma cfDNA 5hmC is a highly sensitive biomarker for common cancer detection. Our genome‐wide analysis of 5hmC in six cancers reveals new target genes and signalling pathways with therapeutic potential for common cancers.